Effects of soilless and soilbased nursery media on seedling emergence, growth and response to water stress of African breadfruit (Treculia africana Decne) - Baiyeri, K.P.; Mbah, B.N. (2006)
The production of high quality seedlings for orchard and plantation establishment involves several cultural inputs. The quality of potting media perhaps stands out as the most important. Therefore, the effects of three soilless media and a soil-based medium on seedling emergence, seedling growth and susceptibility to water stress were studied using African breadfruit as a test crop. Most of the seedling parameters evaluated was significantly influenced by the potting media used. Percent seedling emergence and whole-plant dry matter content were higher in media 1:2:3 ricehull-based (ricehull :poultry manure : river sand, RHB) and 2:3:1 RHB. After induction of water stress, seedling grown in these media remained turgid for a longer period than those grown in media 1:2:3 soil-based (top soil : poultry manure : river sand, SB) and 1:4:3 RHB. Seedlings raised in the soil-based medium were generally poorer in most of the parameters measured. General growth responses and reaction to water stress suggested that media 1:2:3 RHB and 2:3:1 RHB were the best. Seedling grown in these media had delayed water stress symptom expression suggesting a better water economy.